Abdominal Bleeding Ec Suspect Rupture Caecarean Scar Pregnancy - Mardoni Efrijon; Yusrawati, Yusrawati (Fakultas Kedokteran Universitas Andalas, 2025)
Background: Caesarean scar pregnancy (CSP) is a rare form of ectopic pregnancy where the gestational sac implants within the scar of a previous caesarean section. With an estimated incidence of 1/1008 to 1/2500 of all previous caesarean deliveries, CSP can lead to life-threatening complications such as uterine rupture and severe bleeding. Case Presentation: A 27-year-old woman, G3P2A0L2, presented with lower abdominal pain, shortness of breath, and nausea. She had a history of two previous caesarean sections. Physical examination revealed abdominal tenderness and rebound tenderness. Ultrasound suggested a 13-14 week pregnancy with suspected CSP rupture. Emergency laparotomy confirmed uterine rupture at the previous CS scar with placental protrusion. A supravaginal hysterectomy was performed. Discussion: CSP occurs when the blastocyst implants in the lower uterine segment of a previous caesarean scar. Early detection is crucial to prevent severe complications. Transvaginal ultrasound with color Doppler is the primary diagnostic tool. Treatment should aim to remove the gestational sac and CSP mass while preserving fertility when possible. Conclusion: The rising caesarean section rates may lead to increased incidence of CSP. Early diagnosis through transvaginal ultrasound and individualized treatment are essential to reduce morbidity. Clinicians should be aware of this condition and counsel patients about the risks associated with caesarean sections.